2020
DOI: 10.1002/mrm.28604
|View full text |Cite
|
Sign up to set email alerts
|

Toward nonparametric diffusion‐ characterization of crossing fibers in the human brain

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 113 publications
11
40
0
Order By: Relevance
“…Recently, frameworks that combine diffusion tensor MRI and relaxometry have been introduced to improve their specificity for the quantification of myelin and axonal attributes irrespective of the complexity of fiber organization within the voxel, even in the presence of crossing fibers [ 150 , 151 ]. A growing body of evidence also suggests the role of excess iron deposition in the pathology of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, frameworks that combine diffusion tensor MRI and relaxometry have been introduced to improve their specificity for the quantification of myelin and axonal attributes irrespective of the complexity of fiber organization within the voxel, even in the presence of crossing fibers [ 150 , 151 ]. A growing body of evidence also suggests the role of excess iron deposition in the pathology of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Multidimensional MRI is an emerging approach [37] that is now being applied to address a range of medical conditions such as prediction of pregnancy complications via placenta characterization [9], spinal cord injury [6,38], prostate cancer [39], breast cancer [40], and axonal injury due to TBI [22]. Recent in vivo proof-of-concept applications of subvoxel T 1 -T 2 correlation spectra using 105 images [41] and of subvoxel diffusion-T 1 correlation spectra using 363 [11] and 304 [42] images are promising. Here we showed that accurate and robust subvoxel T 1 -T 2 and MD-T 2 correlation spectra can be obtained using only 36 and 122 images, respectively, by using a constrained optimization data processing framework (i.e., MADCO [13]) in conjunction with applying the NESMA filter to reduce noise.…”
Section: Discussionmentioning
confidence: 99%
“… 40 An alternative approach avoids inversion recovery altogether by only varying TR to yield T1 sensitivity. 41 …”
Section: Acquisitionmentioning
confidence: 99%
“…For example, a sequence combining tensor‐valued diffusion encoding with multiple TR weighting was introduced as a means to establish correlations between and diffusion properties and thus characterize complex fiber orientation layouts. 41 However, the combined relaxation and b‐tensor protocols developed thus far have utilized a rather straightforward design, particularly from the relaxation encoding perspective, with suboptimal echo and recovery time samplings. In this regard, there is potential for improvement through combining arbitrary b‐tensor shape with acquisition strategies that encode relaxation information more efficiently.…”
Section: Acquisitionmentioning
confidence: 99%